Best Answer

The sum of any four odd numbers will never be equal to an odd number.

More answers

Lvl 1

5332

Q: What 4 odd numbers equal 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

This is not possible, 27 is an odd number, 4 odd numbers will always equal an even number.

2 odd numbers added together equal an event number. to even numbers added together equal an even number. it is impossible to make 4 odd numbers equal an even.

3721

The sum of the first x odd numbers is equal to x2 (for integers only.) For example, take 72: We'll take the first seven odd numbers: 1 + 3 + 5 + 7 + 9 + 11 + 13 = 4 + 12 + 20 + 13 = 16 + 33 = 49 This then, can be expressed as follows:     x x2 = Σ(2n - 1)    n=1

If the sum of two numbers is even, the two numbers are either both even or both odd. A few examples:2 + 4 = 6 (even + even = even)2 + 3 = 5 (even + odd = odd)5 + 2 = 7 (odd + even = odd)7+13 = 20 (odd + odd = even)

Related questions

This is not possible, 27 is an odd number, 4 odd numbers will always equal an even number.

The sum of any four odd numbers will never be equal to an odd number.

The sum of any four odd numbers will never be equal to an odd number.

2 odd numbers added together equal an event number. to even numbers added together equal an even number. it is impossible to make 4 odd numbers equal an even.

133,135,137,139

Two even numbers never, NEVER equal an odd number. For example, 2+2=4, 150+68= 218, 1,000,000+2= 1,000,002. However, two odd numbers equal an even number. For example, 13+45= 58. It is the same when multiplying negatives and postitives, as seen in Pre Algebra.

There is no set of four consecutive numbers (odd or even) whose sum equals 169.

To add to 13 with 2 even and 1 odd number, can do 1+4+8=13

Adding 4 odd numbers together will always equal an even number - got ya!

3721

The sum of the first x odd numbers is equal to x2 (for integers only.) For example, take 72: We'll take the first seven odd numbers: 1 + 3 + 5 + 7 + 9 + 11 + 13 = 4 + 12 + 20 + 13 = 16 + 33 = 49 This then, can be expressed as follows:     x x2 = Σ(2n - 1)    n=1

13 + 9 = 22 13 - 9 = 4